Perancangan Interleaved Boost Converter Dari 8-12 ke 24V Dengan Umpan Balik Tegangan - Adi Nurcahyo; Sapto Nisworo; Dwi Novianto; Reza Yusuf Kurniawan (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
The use of DC voltage is now increasingly massive with various needs, but the voltage source obtained tends to be unstable to meet the existing electrical load, so it is necessary to adjust the voltage so that it works properly and there is no damage to the load, namely by adding a DC-DC converter system. Because of this basis, this research focuses on how to increase the DC voltage with minimal ripple and according to the voltage requirements in general, namely 12, 24, and 48V. In this study, the authors made a 24V Interleaved Boost Converter with an input value range of 8 to 12V. Tests found that the Interleaved Boost Converter is able to maintain a constant voltage of 24V without oscillation with a voltage feedback control system, the input voltage ripple is 240 mV and the resulting output voltage ripple is 680 mV, while the input current ripple is 800 mA and the output current ripple is 560 mA.